Effectiveness of peer-led educational intervention program in improving knowledge, attitude and practice on Hepatitis-B among undergraduate students in Nigeria - Anka, Yakubu Hussaini (2016)
Introduction: The infectious hepatitis-B virus (HBV) has become one of the most important infectious disease pandemics of this millennium. It is one of the major causes of liver disease morbidity and mortality worldwide, accounting for over 360 million cases of chronic infection and 620,000 deaths yearly. It is hyper-endemic in Sub-Sahara Africa (SSA) causing up to 44% liver disease such as cirrhotic and 47% of hepatocellular carcinomas. In Nigeria, varying estimates of HBV prevalence among different risk groups has been reported. The objectives of the present study were, to develop, implement, and evaluate a peer-led education intervention module on improving knowledge, attitude and practice on HBV among undergraduate students of Usman Danfodiyo University Sokoto Nigeria. Methodology: A randomised single-blind, placebo-controlled community trial study design was used in this study. The study location was Usman Danfodiyo University Sokoto (UDUS) Nigeria. A total of 390 university students were randomly selected and allocated to intervention and the control arms using SPSS computer generated randomization method. The intervention arm received 12-hour peer education program on HBV information and life skill on HBV prevention while the control arm received a session of the importance of physical activities. A validated pretested questionnaire was used to measure knowledge; attitude and practice related to HBV at baseline, immediately post-intervention, three months post intervention and six months post-intervention. Data was analysed using SPSS version 22. Chi-square test was used to test for the homogenity of variance between the intervention and the control arms at baseline. One way ANOVA and two-way repeated measure ANOVA test were used to assess the effectiveness of the intervention. A p-value of less than 0.05 was considered the significance and partial eta square used as a measure of effect size. Results: The results showed there was a significance improvement in respondents HBV knowledge in the intervention arm immediately two weeks after the intervention, three months and six months follow-up assessment with large effect size (partial eta ἠ2 = 0.709, p = 0.001). The intervention was also effective in improving attitude related to HBV at immediately two weeks after the intervention, three months and six months follow-up assessment with large effect size (partial eta ἠ2 = 0.818, p=0.001). Similarly, the intervention module was also effective in improving practice related to HBV at immediately two weeks after the intervention, three months and six months follow-up assessment with large effect size (partial eta ἠ2 = 0.623, p=0.001). Conclusion: The present study is effective in improving knowledge, attitude, and practices of the undergraduate students on HBV infection. The module developed can be adopted by the university as part of their curriculum of studies.